2018
DOI: 10.4103/ijcm.ijcm_56_18
|View full text |Cite
|
Sign up to set email alerts
|

Are school-going adolescents mentally healthy? Case study from Sabarkantha, Gujarat, India

Abstract: Background:Mental health issues becoming the global public health challenge, especially among the youth (12–24 years of age), although they are often detected later in life. In India, the adolescent population constitutes a quarter of the country's population and burden of disease varies from 9.5 to 102/1000 population. Most of the mental health disorders remain unidentified due to negligence and ignorance of multiple factors. Keeping this in mind and lack of population-based studies with good quality for guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 10 publications
1
11
0
Order By: Relevance
“…This finding was comparable with those of Nair, S., who also measured that female participants from Gujarat had higher scores in terms of emotional problems compared with male participants [30]. This finding was also confirmed by Puwar, T. et al [44] and Aboobaker, S. et al in other settings in India [37]; Wang et al [40] in China; and Rimal, H.S. and Pokharel, A. in Nepal [45].…”
Section: Discussionsupporting
confidence: 84%
“…This finding was comparable with those of Nair, S., who also measured that female participants from Gujarat had higher scores in terms of emotional problems compared with male participants [30]. This finding was also confirmed by Puwar, T. et al [44] and Aboobaker, S. et al in other settings in India [37]; Wang et al [40] in China; and Rimal, H.S. and Pokharel, A. in Nepal [45].…”
Section: Discussionsupporting
confidence: 84%
“…The study aimed to identify original research about mental health issues among school children and adolescents aged 19 years and under in India from studies published predominantly between January 2013 and August 2023. To obtain relevant articles, our initial literature search yielded 358 articles, 31 of which were included in this systematic review, the characteristics of which are summarized in The systematic review includes 24 cross-sectional studies [19,20,23,24,[26][27][28][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]46,47], two descriptive cross-section studies [17,18], two comparative cross-section studies [21,29], whereas one randomized control trial [22], one survey study [25], and one intervention study [45] respectively. This review had 30,970 participants, of which 14381 (46.43%) were male.…”
Section: Resultsmentioning
confidence: 99%
“…This review had 30,970 participants, of which 14381 (46.43%) were male. The overall mean age of the school children and adolescents was 14.58 years, with a standard deviation of 1.35 [22,24,[26][27][28][29][35][36][37][38]43,44]. As per participants' concern, the sample size for cross-section studies ranging from 150 to 6682 participants, 242-369 participants for descriptive cross-section studies [17,18] and 462-1000 participants for comparative crosssection studies [21,29], whereas in randomized control trials [22], survey study [25], and intervention study [45], number of participants were 11, 874, and 300 respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, school-age adolescents exhibit high stress levels in everyday life (Mathew et al, 2015). Recent studies have revealed that the prevalence of mental disorders among school-age adolescents in India is rising (Kharod & Kumar, 2015; Mangal et al, 2020; Nair et al, 2017; Puwar et al, 2018; Singh et al, 2017). Previous studies have identified stressors among adolescents, such as the pressure of academic performance, emotional distress resulting from difficulties in forming, maintaining and ending romantic relationships, negotiating autonomy with parents, safety, and risk of sexual harassment, bullying and teasing, among others (Parikh, Michelson et al, 2019).…”
mentioning
confidence: 99%